“It’s harder to catch a boy because they’re tougher”: Using Fairytales in the Classroom to Explore Children’s Understandings of Gender - Paterson, Kate (Alberta Journal of Educational Research, 2015)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; line-height:200%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} p.Abstract, li.Abstract, div.Abstract {mso-style-name:Abstract; mso-style-unhide:no; mso-style-qformat:yes; mso-style-next:Normal; margin-top:.25in; margin-right:28.35pt; margin-bottom:15.0pt; margin-left:.5in; mso-add-space:auto; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} p.AbstractCxSpFirst, li.AbstractCxSpFirst, div.AbstractCxSpFirst {mso-style-name:AbstractCxSpFirst; mso-style-unhide:no; mso-style-qformat:yes; mso-style-next:Normal; mso-style-type:export-only; margin-top:.25in; margin-right:28.35pt; margin-bottom:0in; margin-left:.5in; margin-bottom:.0001pt; mso-add-space:auto; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} p.AbstractCxSpMiddle, li.AbstractCxSpMiddle, div.AbstractCxSpMiddle {mso-style-name:AbstractCxSpMiddle; mso-style-unhide:no; mso-style-qformat:yes; mso-style-next:Normal; mso-style-type:export-only; margin-top:0in; margin-right:28.35pt; margin-bottom:0in; margin-left:.5in; margin-bottom:.0001pt; mso-add-space:auto; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} p.AbstractCxSpLast, li.AbstractCxSpLast, div.AbstractCxSpLast {mso-style-name:AbstractCxSpLast; mso-style-unhide:no; mso-style-qformat:yes; mso-style-next:Normal; mso-style-type:export-only; margin-top:0in; margin-right:28.35pt; margin-bottom:15.0pt; margin-left:.5in; mso-add-space:auto; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; mso-bidi-font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ansi-language:EN-GB; mso-fareast-language:EN-GB;} @page WordSection1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> Traditional fairytales serve to socially construct gendered categories and reify dominant understandings of masculinities and femininities. Using reading groups and participant observations in an elementary school classroom, this article explores how children actively engage with gendered messages within fairytales—specifically examining children’s adherence to, and negotiation of, gender boundaries as demonstrated through their performances of gender within daily classroom discussions and activities. This article illustrates the diverse ways in which children engage with text and how they apply these messages to their own lives, work within its confines, and explore alternatives. Findings demonstrate the potential for educators to create an environment through which children are afforded the freedom to navigate gendered messages and discourses. Such initiatives may contribute to developing more inclusive learning environments and educational opportunities that challenge the perpetuation and reinforcement of long-established gender stereotypes in the classroom. Les contes de fées traditionnelles servent à construire des catégories sociales axées sur le genre et ils réifient les conceptions dominantes de la masculinité et la féminité. Reposant sur les groupes de lecture et les observations de participants dans une école élémentaire, cet article examine l’engagement actif des enfants avec les messages genrés dans les contes de fées, notamment la mesure dans laquelle les enfants respectent et négocient les frontières entre les sexes dans leur comportement pendant les discussions et les activités en classe. Cet article illustre les façons diverses dont les enfants réagissent au texte, mettent en pratique les messages qui s’y trouvent, fonctionnent dans ses limites et explorent des alternatives. Les résultats révèlent le potentiel pour les enseignants de créer un environnement dans lequel les enfants s’orientent en toute liberté face aux messages et aux discours genrés. De telles initiatives pourraient aider le développement de milieux d’apprentissage plus inclusifs et la création d’occasions pédagogiques qui rejettent le maintien et le renforcement de vieux stéréotypes liés au genre dans la salle de classe.